2009
DOI: 10.1515/jpem.2009.22.3.241
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D Nutritional Status of Exclusively Breast Fed Infants and Their Mothers

Abstract: A high prevalence of vitamin D deficiency was found in lactating mothers and their exclusively breast fed infants. Infants born to mothers with hypovitaminosis D had 3.8 times higher risk of developing hypovitaminosis D as compared to those born to mothers with normal vitamin D levels.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
43
1
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(50 citation statements)
references
References 25 publications
5
43
1
1
Order By: Relevance
“…Pregnant mothers, from enrollment at 27 weeks' gestation to birth, and then their infants, from birth to age 6 months, were randomly and equally assigned, to 1 of 3 groups: placebo, or lower-dose or higher-dose vitamin D 3 . Woman/infant pairs received a once-daily oral dose of placebo/ placebo, vitamin D 3 1000 IU/400 IU, or vitamin D 3 2000 IU/800 IU.…”
Section: Trial Designmentioning
confidence: 99%
See 1 more Smart Citation
“…Pregnant mothers, from enrollment at 27 weeks' gestation to birth, and then their infants, from birth to age 6 months, were randomly and equally assigned, to 1 of 3 groups: placebo, or lower-dose or higher-dose vitamin D 3 . Woman/infant pairs received a once-daily oral dose of placebo/ placebo, vitamin D 3 1000 IU/400 IU, or vitamin D 3 2000 IU/800 IU.…”
Section: Trial Designmentioning
confidence: 99%
“…1 Vitamin D status at birth and during early infancy, when breast milk is the predominant source of nutrition, is determined by maternal vitamin D status. 2,3 Contemporary population-and primary care-based studies of pregnant women have shown a high prevalence of serum 25(OH)D ,20 ng/mL in Asia (70%-96%), [4][5][6] Australia (10%-47%), [7][8][9][10] Europe (15%-44%), 11,12 the United Kingdom (49%-75%), [13][14][15] India (74%), 16 and the United States (37%). 17 Although less completely studied at the population level, in primary care-based studies from the United States, serum 25(OH)D ,20 ng/mL is present in 11% to 12% of infants.…”
mentioning
confidence: 99%
“…1,2 Pregnant and lactating women and their newborn infants are at a high risk of vitamin D deficiency. [3][4][5][6][7][8][9][10][11][12] Vitamin D is involved in skeletal homeostasis during pregnancy. 13,14 Severe vitamin D deficiency with profound hypocalcemia may lead to seizures in neonates, and has also been associated with low birth weight, prenatal death, preeclampsia and an increased risk of primary cesarean section.…”
Section: Introductionmentioning
confidence: 99%
“…5 There are a few reports of vitamin D deficiency among pregnant women and cord blood of their newborns and breastfed young infants from India. [6][7][8][9] So this study was undertaken to study the serum vitamin D levels in exclusively breastfed babies and their mothers in a tertiary care hospital. Aims and objectives of present study were to study the serum vitamin D levels among exclusively breastfed infants aged 3-6 months, to study the serum vitamin D levels among their lactating mothers and to study the correlation between the serum vitamin D levels of exclusively breastfed infants and their mothers.…”
Section: Introductionmentioning
confidence: 99%